2019
DOI: 10.1124/dmd.119.086611
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Components of Cardiac Metabolism

Abstract: Metabolism in organs other than the liver and kidneys may play a significant role in how a specific organ responds to chemicals. The heart has metabolic capability for energy production and homeostasis. This homeostatic machinery can also process xenobiotics. Cardiac metabolism includes the expression of numerous organic anion transporters, organic cation transporters, organic carnitine (zwitterion) transporters, and ATP-binding cassette transporters. Expression and distribution of the transporters within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 220 publications
0
17
0
Order By: Relevance
“…ABC transporters are a series of ATP-dependent transport enzymes, which can transport multiple endogenous compounds including amino acids, ions, and nucleotides. Researchers have found that ABC transporters are involved in the homeostasis of the heart [29]. We found that the transport of amino acids (e.g., glutamate) was altered after MI.…”
Section: Plos Onementioning
confidence: 71%
“…ABC transporters are a series of ATP-dependent transport enzymes, which can transport multiple endogenous compounds including amino acids, ions, and nucleotides. Researchers have found that ABC transporters are involved in the homeostasis of the heart [29]. We found that the transport of amino acids (e.g., glutamate) was altered after MI.…”
Section: Plos Onementioning
confidence: 71%
“…ABC transporters are a family of ATP-dependent transporters that can transport a variety of endogenous compounds, including amino acids, ions, nucleotides, lipids, and peptides, across the cell membrane. Researchers have found that ABC transporters are altered after MI and are involved in cardiac homeostasis [ 33 , 34 ], which constitute future research directions regarding the cardioprotective effect of proline metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters are a family of ATPdependent transporters that can transport a variety of endogenous compounds, including amino acids, ions, nucleotides, lipids, peptides, and so on, across the cell membrane. Researchers have found that ABC transporters are altered after MI and are involved in cardiac homeostasis [31], [32], which constitute future research directions regarding the cardioprotective effect of proline metabolism.…”
Section: Discussionmentioning
confidence: 99%